INCREASING COMMUNITY PARTICIPATION ACTIVITY THROUGH LEARNING MENTORING - Fukrotutsauroh, Aas (Universitas Djuanda, 2016)
Real Working Lecture (KKN) is one of dedication to the community in which students toapply knowledge and skills they have significantly according to their areas of expertise. RealWork Lecture is a form of manifestation of Tri Dharma College .In learning activities areexpected to increase the Participation of society through activities that exist in society. KKNstudents participating in the Faculty of Education in collaboration with the University ofDjuanda Bogor sub district community Susukan Bojonggede Bogor Regency to utilizecommunity resources in implementing the mentoring program belajar. Kuliah Real Work(KKN) conducted by the Faculty of Education University of Djuanda Bogor expected toincrease public participation in the activities of tutoring for the creation of an effective andefficient learning.